Acetabular impaction grafting with mesh for acetabular bone defects: a systematic review. Issue 2 (March 2022) - Malahias, Michael-Alexander; Mancino, Fabio; Gu, Alex; Adriani, Marco; De Martino, Ivan; Boettner, Friedrich; Sculco, Peter K
Introduction: In conjunction with impaction bone grafting (IBG), metal meshes have been proposed to minimise defects of the medial and superolateral walls in order to convert combined complex uncontained segmental defects into contained cavitary defects to facilitate IBG. Methods: The US National Library of Medicine (PubMed/MEDLINE), EMBASE, and the Cochrane Database of Systematic Reviews were queried for publications from January 1980 to March 2019 utilising keywords pertinent to total hip arthroplasty (THA), acetabular impaction bone grafting, clinical or functional outcomes, revision THA, or postoperative complications. Results: 7 articles were found to be suitable for inclusion in the present study. The mean modified Coleman methodology score for methodological deficiencies of the studies was 45.3 (range 38–59). Severe acetabular bone loss was present in 56% of cases having moderate bone loss in 18%, and mild in 26%. The all-cause reoperation rate was 7.4%, while the all-cause revision rate of the acetabular component was 6.2%. Conclusions: IBG with mesh is effective for selected patients with acetabular bone defects. Most patients with moderate bone loss as well as selected patients with large superolateral defects can be successfully treated with IBG combined with mesh. There is limited data to show that IBG with mesh might be associated with decreased survival rates in patients with severe lateral defects (Paprosky IIIA) combined with ischial or medial wall osteolysis who require combined medial and lateral meshes. In addition, patients with severe superomedial migration of the cup (Paprosky IIIB) should not be treated with IBG and mesh.